Extending the phenotype associated with the CSNK2A1‐related Okur–Chung syndrome—A clinical study of 11 individuals. Issue 5 (31st January 2018) - Owen, Ceris I.; Bowden, Ramsay; Parker, Michael J.; Patterson, Jo; Patterson, Joan; Price, Sue; Sarkar, Ajoy; Castle, Bruce; Deshpande, Charulatha; Splitt, Miranda; Ghali, Neeti; Dean, John; et al.
Abstract : Variants in the Protein Kinase CK2 alpha subunit, encoding the CSNK2A1 gene, have previously been reported in children with an intellectual disability and dysmorphic facial features syndrome: now termed the Okur–Chung neurodevelopmental syndrome. More recently, through trio‐based exome sequencing undertaken by the Deciphering Developmental Disorders Study (DDD study), a further 11 children with de novo CSNK2A1 variants have been identified. We have undertaken detailed phenotyping of these patients. Consistent with previously reported patients, patients in this series had apparent intellectual disability, swallowing difficulties, and hypotonia. While there are some shared facial characteristics, the gestalt is neither consistent nor readily recognized. Congenital heart abnormalities were identified in nearly 30% of the patients, representing a newly recognized CSNK2A1 clinical association. Based upon the clinical findings from this study and the previously reported patients, we suggest an initial approach to the management of patients with this recently described intellectual disability syndrome.